Chemical study of the Ayahuasca Liana (Banisteriopis caapi) - Reyna pinedo, Víctor (2002)
From the stem of the liana Ayahuasca (Banisteriopsis caapi) harmina was obtained, wish was identified by its fusion point, the percent analysis of its elements, and the mass spectra RMN'H. RMNBC, IR and UV. Furthermore, the qualitative analysis of the secondary metabolites was done, as well as the analysis to determine the amount of alkaloids present in the plant.